Penang Young Viewers’ Interest And Perception Toward Local Mesomorphic Superhero Design (LMSD) - Khor, Teong Siang (2024)
The purpose of this study is to understand and analyse how Penang's young viewers perceive and interest in local mesomorphic superhero designs (LMSD). The study begins by looking into the origins of local young people and superheroes, followed by several local professionals were interviewed to further support the idea and significance of the study.